The Utilization of 18650 Laptop Batteries for Developing Series-Parallel Circuit Practicum Tools - Mohammad Djamil M. Nur; Siti Rabiatul Adawiyah; Ummi Khoiriyah (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to first understand the design of the series-parallel of practicum tools by utilizing the used battery of the 18650 Laptop. Second, determine how effectively the series-parallel circuit practicum tools use 18650 laptop batteries. This research is research and development (R&D). The research stages include preliminary studies, product planning and design, product validation and revision, and product tests and revisions. The sample consisted of students from the 2022, 2023, and 2024 batches of the Tadris Science Study Program of FTIK UIN Datokarama Palu. The sampling technique used is purposive sampling. The data was collected through interviews, observations, documentation, and questionnaires. The research results were obtained from a practicum tool product consisting of a series-parallel circuit board, voltmeter ammeter digital-based, and input voltage sourced from a used 18650 battery. The results of product validation tests that material experts have carried out have a percentage of 95% with a very feasible category, and media experts have obtained a rate of 95.83% with a Very suitable category. The revised product was then initially tested to receive an assessment percentage of 94.26% in the Very suitable category. Field tests with a limited scale were conducted using revised products with a 98.57% assessment percentage in the Very suitable category. Products that have been made are suitable for use in series-parallel circuit practicums.